POLITIK PLURALITAS DAN DEMOKRATISASI MEDIA DALAM PENGUATAN MASYARAKAT SIPIL - Imam Sofyan (Jurusan Ilmu Komunikasi UTM, 2015)
Democratization in every aspect of life as well as the impact of the demandsof the process of political change is considered positive or negative impactfor changes in society, especially for developing countries, which are intransition to developed countries to be desired, which characterized theopenness of society. A country that is also expected to provide assurance andcompliance for penyejahteraan society (welfare state). This article intendsto describe theoretically the political concept of plurality in the context ofIndonesian society follows the role of the media in achieving democratizationand strengthening civil society.Keywords: political plurality, the democratization of the media, civil society